1996
DOI: 10.1063/1.117077
|View full text |Cite
|
Sign up to set email alerts
|

Inductively coupled plasma etching of GaN

Abstract: Inductively coupled plasma (ICP) etch rates for GaN are reported as a function of plasma pressure, plasma chemistry, rf power, and ICP power. Using a Cl2/H2/Ar plasma chemistry, GaN etch rates as high as 6875 Å/min are reported. The GaN surface morphology remains smooth over a wide range of plasma conditions as quantified using atomic force microscopy. Several etch conditions yield highly anisotropic profiles with smooth sidewalls. These results have direct application to the fabrication of group-III nitride e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
88
0
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(91 citation statements)
references
References 0 publications
1
88
0
2
Order By: Relevance
“…When the power was increased to 150 W, the Pt (0) content is reduced (45.34%) and lower than that of 100 W (49.10%), which suggests that some amount of Pt (0) was removed from sample under excessive power due to etching effect of H 2 plasma. 32 The X-ray diffraction (XRD) patterns of Pt/P-rGO under different power conditions are observed that the diffraction peaks at 39.8 o , 46.4 o and 67.9 o correspond to Pt (111), (200) and (220) facets of face-centered cubic Pt crystals respectively (FIG. 2(b)).…”
Section: Resultsmentioning
confidence: 99%
“…When the power was increased to 150 W, the Pt (0) content is reduced (45.34%) and lower than that of 100 W (49.10%), which suggests that some amount of Pt (0) was removed from sample under excessive power due to etching effect of H 2 plasma. 32 The X-ray diffraction (XRD) patterns of Pt/P-rGO under different power conditions are observed that the diffraction peaks at 39.8 o , 46.4 o and 67.9 o correspond to Pt (111), (200) and (220) facets of face-centered cubic Pt crystals respectively (FIG. 2(b)).…”
Section: Resultsmentioning
confidence: 99%
“…The best reported selectivity for GaN on AlN of 38 was obtained using Cl 2 /Ar mixture at -20 V bias [27]. Highly anisotropic profiles with smooth sidewalls in GaN have been reported by Shul et al [25]. A vertical etch profile with ultra-smooth sidewall in InGaN/AlGaN heterostructure obtained with a regrown oxide mask is shown in Fig.…”
Section: Etch Rates and Profilesmentioning
confidence: 94%
“…As expected, high etch rates and etch profiles with high anisotropy have been demonstrated. Etch rates of GaN as high as 688 nm/min at -280 V [25] and 980 nm/min at -450 V [27] have been reported for Cl 2 /H 2 /Ar and Cl 2 /Ar plasmas, respectively. A GaN etch rate of 850 nm was obtained using BCl 3 /Cl 2 plasma at -120 V and 30 mTorr [26].…”
Section: Etch Rates and Profilesmentioning
confidence: 99%
See 2 more Smart Citations